دراسة بعض استخدامات التنوع الحيوي النباتي وأهم النشاطات البشرية المؤثرة به في محمية أبي قبيس - الشاطر زهير; المحمود فادي (Latakia University Journal -Biological Sciences Series, 2019)
تمت دراسة بعض استعمالات التنوع الحيوي النباتي في محمية أبي قبيس على السفح الشرقي للجبال الساحلية خلال عامي 2008-2009. تم تحديد 24 نوعاً مأكولاً و30 نوعاً تزيينياً و 30 نوعاً ساماً و46 نوعاً طبياً وعطرياً و145 نوعاً مستساغاً للرعي من أصل 509 نوعاً مسجلاً في المحمية. من ناحية أخرى, تم العثور على 12 نوعاً من الفصيلة السحلبية وأنواعاً أخرى ذات أهمية خاصة في المحمية. أظهرت الدراسة كذلك تعرض جزء كبير من المحمية لدرجة عالية من النشاط البشري (رعي جائر واقتطاع) والذي يتمحور حول القرى بشكل أساسي. تعتبر هذه النتائج محورية في تقسيم المحمية إلى مناطق وفي إدارة التنوع الحيوي النباتي في المحمية. Some uses of plant species diversity have been studied and evaluated in Abu-Qubies protected area in the eastern slope of the coastal mountains of Syria in the period between 2008-2009. From the 509 species of the protected area 24 edibles, 30 ornamental, 30 poisonous, 46 medicinal , aromatic and 145 grazed species have been identified. On the other hand, 12 species of the familly of Orchidaceae have been found in the protected area with many other important species. The study has also shown that the protected area is affected by a high degree of human activity (overgrazing and wood cutting) which is concentrated mainly around the villages. These results are very important in the zoning process and the biodiversity management of the protected area.